2004
DOI: 10.1254/jphs.94.207
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Treatment With the Traditional Medicine Unsei-in Inhibits Substance P-Induced Itch-Associated Responses Through Downregulation of the Expression of Nitric Oxide Synthase 1 in Mice

Abstract: Abstract. Unsei-in inhibits substance P (SP)-induced scratching of mice after repeated administration. The involvement of cutaneous nitric oxide (NO) in the SP-induced scratching led us to investigate the effects of Unsei-in on the cutaneous NO system in mice. Seven-day oral administration of Unsei-in (300, but not 100, mg / kg daily) significantly inhibited scratching and the increase of cutaneous NO after intradermal SP injection. The NO synthase 1 (NOS1) inhibitor 7-nitroindazole (1 nmol / site) decreased S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…showed that Unseiin inhibited substance P‐induced itch‐associated response through the suppression of neurokinin‐1 tachykinin receptor expression . They also suggested that the inhibition of cutaneous nitric oxide synthase‐1 expression and nitric oxide production participated in the antipruritic action of Unseiin . In the present case, these mechanisms might have contributed to the antipruritic effects of Unseiin followed by improvement of skin eruptions.…”
Section: Discussionsupporting
confidence: 58%
“…showed that Unseiin inhibited substance P‐induced itch‐associated response through the suppression of neurokinin‐1 tachykinin receptor expression . They also suggested that the inhibition of cutaneous nitric oxide synthase‐1 expression and nitric oxide production participated in the antipruritic action of Unseiin . In the present case, these mechanisms might have contributed to the antipruritic effects of Unseiin followed by improvement of skin eruptions.…”
Section: Discussionsupporting
confidence: 58%
“…In mice, nitric oxide may be as an itch enhancer and increases scratching induced by substance P (36) and medicine that decreases nitric oxide in the skin inhibits substance Pelicited scratching (37). However, the ESGM-elicited scratching was not suppressed by N G -nitro-L-arginine methyl ester at a dose that had been shown to suppress scratching induced by substance P (36), suggesting that nitric oxide is not involved in mosquito allergyassociated itching.…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction, electrophoresis, and membrane transfer were done as described (12). The transferred membrane was reacted with anti-PAR 2 monoclonal antibody (SAM-11, 1:500; Santa Cruz Biotechnology) and anti-β-actin monoclonal antibody (1:5,000, Sigma).…”
Section: Western Blottingmentioning
confidence: 99%